Strengthening the statistical assessment of university social responsibility and sustainable development goal integration in higher education institutions - Donado, Mildred Garizabal; Campo, Mauro Maury; Arias, Luis Fernando Ospino; Donado, Luz Garizabal (Global Journal of Social Sciences Studies, 2026)
This study aims to examine how higher education institutions in Barranquilla, Colombia, integrate University Social Responsibility with the Sustainable Development Goals, emphasizing not only the visibility of institutional initiatives but also the need for stronger empirical assessment of their coherence, implementation, and perceived impact. The study adopts a quantitative, non-experimental, field-based, and descriptive design, using survey data collected from members of the university community across selected higher education institutions. Responses were organized through Likert-type items and analyzed using descriptive statistics, including percentage distributions, favorable and unfavorable response groupings, and estimated mean scores, with the results structured around sustainability initiatives, inclusion policies, academic integration, strategic planning, institutional management, communication, and accountability mechanisms. The findings show that respondents generally perceive meaningful progress in sustainability-oriented activities, volunteering, inclusion, environmental practices, and institutional values linked to social responsibility. However, the evidence also reveals persistent weaknesses in impact measurement, strategic formalization, periodic reporting, internal communication, and the visibility of specialized structures responsible for coordinating University Social Responsibility and Sustainable Development Goal integration. These results suggest that universities have advanced more clearly in normative commitment and institutional discourse than in consolidated systems of governance, monitoring, and evaluation. The study provides practical implications for university leaders by highlighting the need to strengthen accountability frameworks, improve communication strategies, institutionalize impact assessment, and develop more rigorous statistical procedures for evaluating the relationship between social responsibility practices and sustainable development commitments.